STRATEGY TO BUILD RELIGIOUS VALUES IN STUDENTS AT MTS MIFTAHUL ULUM RENES WIROWONGSO AJUNG JEMBER - Halid, Ahmad (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
This article describes strategies to build religious values in students. Therefore, education at MTS Miftahul Ulum is an effective means in forming students' knowledge and forming religious attitudes in students. This research was conducted at MTS Miftahul Ulum Renes Wirowongso Ajung Jember using descriptive qualitative methods. The results of this study are very important to be developed in schools because student religion is one of the student abilities that must be possessed by every student and becomes a learning program that must be planned by every teacher before starting learning in class. One indication of the success of learning and the achievement of school goals if the religious competence of students is achieved well in the learning process at school.